Analysis of Students Competency in the Industrial Engineering Study Program South Aceh Polytechnic in Mastering the Concept Survey and Mapping Courses - Arinal Ihsan; Sukma Achriadi (LPPM Politeknik Aceh Selatan, 2021)
The problem formulation in this research are a) what is the level of students' ability in mastering the concept of Survey and mapping ?, and b) what difficulties do students experience in mastering the concept of Survey and Mapping?. The research approach uses both quantitative and qualitative approaches. The research procedure goes through several stages, namely a) preparation stage, b) problem formulation stage, c) data collection stage, d) data analysis stage, and e) research results. The population in this study is students of the Industrial Engineering Study Program of South Aceh Polytechnic, while samples are students of semester II of the Academic Year 2020/2021 Industrial Engineering Study Program as many as 1 (one) class. Research is conducted at South Aceh Polytechnic. The instruments in this research are test questions and interview guidelines. Data collection techniques in this study used tests and interviews. Hypothesis testing of students' ability level in understanding survey and mapping subjects (tests) using right-hand t-test at a significance level of 0.05 with acceptance criteria H0 if t t(1-α) and H0 declined for t other values. Interview data were analyzed with the following stages 1) reducing the data, 2) presenting the data, and 3) concluding the data. External must be in the form of an accredited national journal ranked 1- 6 which is published in the Journal of Innovation and Engineering Technology with the information accepted/published. Technology Readiness Level (TKT) is 3. The results of data analysis performed at a significant level α = 0,05 gained and = 1,73, so or 2,51 > 1,73. Thus, it can be concluded that students of the Industrial Engineering Study Program of South Aceh Polytechnic are able to master the concept of survey and mapping courses